Evaluation of electronic state of Cs-adsorbed clay minerals by NEXAFS analysis using DFT calculations. (April 2019) - Suzuki, Chikashi; Yaita, Tsuyoshi; Suzuki, Shinichi; Pacold, Joseph; Altman, Alison B.; Minasian, Stefan G.; Tyliszczak, Tolek; Shuh, David K.; Yoshida, Hiroyuki; Osaka, Masahiko
Abstract: A combined analytical method of NEXAFS measurement and DFT-calculation was employed for the evaluation of Cs states in clay minerals. The measured Cs M4, 5 NEXAFS spectra of Cs halides were analyzed using the DFT-calculations in order to establish the analytical methods. The NEXAFS spectra of the Cs halides were well reproduced by incorporating the core-hole strength. The Cs M4, 5 NEXAFS spectrum of the clay minerals was well reproduced by the DFT-calculations including the major transitions and tail structures with the established method. Further evaluation of this spectrum by charge density analysis suggested that these major transitions and the tail structures likely reflect the bonding state and the local environment around the Cs atoms. Comparison of electronic states of Cs in the clay mineral with those in the Cs halides by DFT-calculations has shown that the interaction between Cs and the nearest-neighbor atom is largest in the clay mineral, which differs from those of Cs halides. This happened due to the energy level of Cs-5s and 5p, which was closer to that of O-2s and 2p than the s and p orbitals of other alkali metal and alkali earth metal elements. Graphical abstract: Image 1 Highlights: The Cs M4, 5 NEXAFS spectra of the Cs halides are well reproduced by incorporating the CHS. The Cs M4, 5 NEXAFS spectrum of the clay minerals was well reproduced by the DFT-calculations using CHS. This spectrum of the clay minerals likely reflect the bonding state and the local environment around the Cs atoms.